PERSONALISED MEDICINE IN BRONCHIAL ASTHMA: CURRENT CONCEPTS AND PROSPECTS - R.M. FAYZULLINA; V.V. VIKTOROV; R.R. GAFUROVA (Avicenna Tajik State Medical University, 2021)
Bronchial asthma (BA) is today a global medical and socio-economic issue in the health care system. Manifesting in childhood, the disease persists throughout the patient's life, characterised by a variable clinical course. The periods of remission are combined with the periods of exacerbation and a wide range of symptoms ranging from mild symptoms to severe illness. Following the data of epidemiological studies, BA occupies a leading place among the chronic disorders of the lungs of non-infectious aetiology with increasing the annual prevalence trend. The article presents a literature review on the prospects for a personalised medicine (PM) approach for the group of socially significant, multifactorial diseases, including BA. Implementing PM for asthma patients makes it possible to diagnose and predict the disease even at the preclinical stage. This will reduce mortality, morbidity and disability rates, cut the costs of treatment and rehabilitation of symptomatic patients, and increase the patient's adaptive capabilities, coping with outdoor environmental and local factors.